2012
DOI: 10.1590/s0104-11692012000600019
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of nursing professionals towards suicidal behavior: influence of emotional intelligence

Abstract: Actitudes del profesional de enfermería hacia el comportamiento suicida: influencia de la inteligencia emocionalObjetivo: Evaluar la actitud y la influencia de la inteligencia emocional es el objetivo de este trabajo. Método: Profesionales de enfermería contestaron un cuestionario que evaluó la actitud hacia el suicidio e inteligencia emocional. Resultados: Los resultados muestran una actitud general desfavorable hacia el comportamiento suicida. La dimensión moral del suicidio marca las diferencias entre los p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
3
22

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 15 publications
(32 reference statements)
3
29
3
22
Order By: Relevance
“…(13,17) Education in mental health and suicide appears to promote consistent improvements in attitude and knowledge related to suicide. (7,15) In the present study, participation in events, courses and lectures on suicide was not associated with better attitudes. On the other hand, attending a psychiatric nursing course or a suicide class and laboratory was associated with a greater perception of professional capacity, but it was not associated with more positive or less condemnatory atti- (19,20) …”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…(13,17) Education in mental health and suicide appears to promote consistent improvements in attitude and knowledge related to suicide. (7,15) In the present study, participation in events, courses and lectures on suicide was not associated with better attitudes. On the other hand, attending a psychiatric nursing course or a suicide class and laboratory was associated with a greater perception of professional capacity, but it was not associated with more positive or less condemnatory atti- (19,20) …”
Section: Discussioncontrasting
confidence: 54%
“…In the literature, a variety of results related to attitudes about suicide between men and women are found. (13) One study identified a less moralistic attitude (15) among women, while in other investigations, there was no difference in attitudes according to sex. (13,17) Education in mental health and suicide appears to promote consistent improvements in attitude and knowledge related to suicide.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…No entanto, é importante considerar que as ações de cuidado desenvolvidas pela equipe de enfermagem ao paciente com risco de suicídio também envolvem um cotidiano rodeado por questões pessoais do profissional, que podem também trazer dificuldades no processo de identificação e classificação dos pacientes. Nesse sentido, o autoconhecimento sobre as emoções poderá contribuir para o manejo do paciente com esse risco (7) . Diante do exposto, o presente estudo tem por objetivo identificar ações de cuidado de enfermagem implementadas a pacientes com risco de suicídio internados em uma Unidade de Internação Psiquiátrica.…”
Section: Introductionunclassified
“…Diante do ambiente estressante dos serviços de emergência e urgência, a dinâmica do trabalho e grande demanda de pacientes faz com que muitos profissionais estejam despreparados para lidar com as vítimas de tentativas de suicídio. E orientações e acolhimento às famílias são pouco abordadas no momento do atendimento, no qual se prioriza a busca de informações sobre o fenômeno ocorrido 17,19,26 . Neste contexto, a finalidade do cuidado ao paciente com comportamento suicida deve ser a redução do fluxo hospitalar, a educação em saúde, a promoção da saúde, e a prevenção, importante para redução de agravos à saúde, mas com relação ao indivíduo que tem comportamentos suicdas, pouco se sabe sobre atividades preventivas 23,26,27 .…”
unclassified